What's left before participatory modeling can fully support real-world environmental planning processes: A case study review. (September 2021) - Hedelin, B.; Gray, S.; Woehlke, S.; BenDor, T.K.; Singer, A.; Jordan, R.; Zellner, M.; Giabbanelli, P.; Glynn, P.; Jenni, K.; Jetter, A.; Kolagani, N.; et al.
Abstract: In environmental participatory modeling (PM), both computer and non-computer-based modeling techniques are used to aid participatory problem description, solution, and decision-making actions in environmental contexts. Although many PM case studies have been published, few efforts have sought to systematically describe and understand dominant PM processes or establish best practices for PM. As a first step, we have reviewed a random sample of environmental PM case study articles (n = 60) using a novel PM process evaluation instrument. We found that significant work likely remains for PM to fully support participatory and integrated planning processes. While PM reports systematically address knowledge integration and learning, they often neglect the facilitation of a multi-value perspective within a democratic process, and the integration across organizations within a governance system. If not reported, we suspect these aspects are also neglected in practice. We conclude with key research and practice issues for improving PM as an approach for real-world participatory planning and governance. Highlights: We developed a novel instrument for evaluating participatory modeling, and we used it to review 60 case studies. The Sustainable Process Framework articulates goals for participatory planning processes. The only aspect reported by nearly all studies was methods for identifying & integrating knowledges. Environmental participatory modeling reports & perhaps processes need significant improvement.